SOURCES OF SPATIAL INFORMATION ABOUT NOISE AS EXEMPLIFIED BY THE SPATIAL INFORMATION SYSTEM (SIS) IN POZNAŃ - Kubiak, Jarosław (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
Noise is subject to compulsory mapping. Access to environmental acoustical data should be available to the public user. These tasks result directly from the provisions of the Environmental Protection Law Act – EPL Act. The method of their implementation is presented using the example of the Poznań Spatial Information System. Available data sources are indicated, mainly in relation to cartographic visualisation of the presented contents.